The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1515/prilozi-2015-0076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Dexamethasone as a Ropivacaine Adjuvant in Ultrasound-Guided Transversus Abdominis Plane Block for Inguinal Hernia Repair

Abstract: Background: The transverses abdominals plane block (TAP) is a regional anesthesia technique that provided analgesia to the parietal peritoneum, skin and muscles of the anterior abdominal wall. The aim of this randomized double-blind study was to evaluate postoperative analgesia on patients undergoing open inguinal hernia repair under general anesthesia (GA), (GA + TAP) block preformed with ropivacaine and (GA + TAP-D) block preformed with ropivacaine and 4 mg dexamethasone. Methods: 90 (ASA I-II) adult patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 20 publications
(18 reference statements)
3
26
0
Order By: Relevance
“…The literature search identified 354 studies, including 9 qualifing RCTs with a total of 575 patients that met the inclusion criteria ( Fig 1 ) [ 16 , 17 , 24 30 ]. The characteristics of patients and interventions are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search identified 354 studies, including 9 qualifing RCTs with a total of 575 patients that met the inclusion criteria ( Fig 1 ) [ 16 , 17 , 24 30 ]. The characteristics of patients and interventions are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All 9 RCTs compared the TAP block using LA with dexamethasone versus LA alone. All studies used a long-acting LA for the TAP block, including bupivacaine in 3 studies [ 26 , 28 , 29 ], ropivacaine in 5 studies [ 16 , 17 , 24 , 25 , 30 ], and levobupivacaine in 1 study [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Duration of prolongation of analgesia with dexamethasone is highly variable with few studies suggesting analgesia up to 20–24 h while others suggest only up to 12–16 h as observed in this study. [ 8 15 16 ] Furthermore, it has also been found that dexamethasone at doses more than 0.1 mg/kg is an effective adjunct in multimodal strategies to reduce post-operative pain and opioid consumption after surgery. [ 17 18 ] Considering the fact that doses <0.1 mg/kg failed to produce any opioid-sparing effect when administered IV, combined with the result of the study conducted by Desmet et al .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the transverse abdominis plane block (TAPB) is a relatively novel procedure for applying local anesthetics into the anatomic neurofascial space and provides analgesia to the skin, muscles of the anterior abdominal wall, and parietal peritoneum. Specifically, it offers a significantly prolonged duration of analgesia during the early postoperative stage [ 13 , 14 ], and reduces opioid consumption after abdominal surgery [ 15 ], suggesting the potential use for elderly patients undergoing open gastrointestinal surgery.…”
Section: Introductionmentioning
confidence: 99%